The study of crime and its relation to the development - Elvi Zuriyani; Rika Despica (Masyarakat, Kebudayaan dan Politik, 2020)
This study discusses the crimes that have occurred in Padang city and their relationship with the development of the city itself. This study used a descriptive spatial approach. The data on crime obtained from Pos Metro Padang newspaper, which specifically contains criminal news from 2015-2016. The data on the development of Padang city was taken from a literature study using a Central Bureau of Statistics or Badan Pusat Statistik (BPS) report. The study used indicators such as the economic level of the region, population data, population density, regional infrastructure, and any linkages with other regions. The results of this study involved the dominant crimes in Padang city of theft, illegal drugs, and immorality. The results showed that there were six sub-districts with high crime rates in 2015 and 2016, including West Padang, South Padang, Lubuk Begalung, Kuranji, East Padang, and Koto Tangah. West Padang and South Padang are downtown areas with high levels of economic activity. East Padang, Lubuk Begalung, Kuranji, and Koto Tangah are the suburban areas of Padang, which also have high population density levels. These areas focused around an education center in Padang City. Based on the results, there is a link between the development of the region and criminal activity. With the presence of various activities in the downtown area, densely populated people and the large number of activities that take place in suburban areas will result in the emergence of various attractions that makes people interested in coming to the region. It is also one of the factors that can trigger criminal acts in Padang city.